A importância de discutir sobre bullying e a violência virtual nas escolas: utilizando a ferramenta “e se fosse com você?” - CUNHA, Marciela Silva da (Instituto Federal do Amapá, 2021)
The school environment is the place where most cases of bullying occur, and with the inclusion of technology in everyday life, it begins to migrate to digital media being known as cyberbullying or virtual violence. And this type of aggression is practiced through the Internet against someone through communication tools related to the virtual world such as social networks, text messages and digital games. Unfortunately, the technological means that would be to improve and facilitate people's lives in all areas, they end up being used to despise and insult other people. This way the defamations are intentional and aim to mess with the person's psychological, leaving him/her down and demoralized before the others. Since these people may grow up with negative feelings, to which they may assume an aggressive behavior that they may later suffer or practice bullying at work. In extreme cases, some of these young people may attempt or commit suicide. The work begins by raising awareness with school staff, students, parents, and the community. The educational community should promote interpersonal or intergroup relationships. Thus, developing programs, solidarity and fraternal projects are preventive forms of human rapprochement and developing affective bonds among their peers. This dissertation addresses the importance of discussing bullying and virtual violence in schools using the "and if it were up to you" tool, as well as creating strategies, informing, debating and sharing experiences so that this type of violence can be avoided in educational institutions.